Application of High-Tech Methods in Surgical Treatment of Patients with Chronic Rhinitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Chronic nasal congestion caused by swelling of the inferior turbinate, which significantly affects the quality of life, affects 20% of the population. Drug treatment of chronic rhinitis is considered the starting therapy, but if conservative treatment methods are ineffective and complaints of difficulty in nasal breathing persist as the predominant symptom, the question arises of choosing the optimal type of surgical intervention on the inferior turbinates.